The usefulness of infrared spectroscopy and X-ray powder diffraction in the analysis of falsified, illegal, and medicinal products - Mocarska, Anna; Piorunska, Karolina; Maurin, Jan K.; Blazewicz, Agata (Frontiers in Chemistry, 2025)
One way to combat the black pharmaceutical market is to exchange experience and knowledge among the laboratories involved in this fight. A beneficial approach is compiling application examples that demonstrate the development and growing potential of the two analytical techniques that are undoubtedly useful in investigating pharmacologically active ingredients found in products dangerous to consumers health and life. Attenuated total reflectance Fourier transform infrared spectroscopy and X-ray powder diffraction are nondestructive techniques substantial for examining evidence seized by the police, demanding minimal preparation of the sample. Importantly, they are among the few that do not negatively impact the environment because they do not require the production or disposal of chemical reagents or solvents, aligning with the principles of green chemistry. Both techniques provide consistent, reproducible results, essential for legal and scientific validity.